Dopamine inhibits lipopolysaccharide-induced nitric oxide production through the formation of dopamine quinone in murine microglia BV-2 cells - Yasuhiro Yoshioka; Yuta Sugino; Azusa Tozawa; Akiko Yamamuro; Atsushi Kasai; Yuki Ishimaru; Sadaaki Maeda (Elsevier, 2016)
Dopamine (DA) has been suggested to modulate functions of glial cells including microglial cells. To reveal the regulatory role of DA in microglial function, in the present study, we investigated the effect of DA on lipopolysaccharide (LPS)-induced nitric oxide (NO) production in murine microglial cell line BV-2. Pretreatment with DA for 24 h concentration-dependently attenuated LPS-induced NO production in BV-2 cells. The inhibitory effect of DA on LPS-induced NO production was not inhibited by SCH-23390 and sulpiride, D1-like and D2-like DA receptor antagonists, respectively. In addition, pretreatment with (−)-(6aR,12bR)-4,6,6a,7,8,12b-Hexahydro-7-methylindolo[4,3-a]phenanthridin (CY 208-243) and bromocriptine, D1-like and D2-like DA receptor agonists, respectively, did not affect the LPS-induced NO production. N-Acetylcysteine, which inhibits DA oxidation, completely inhibited the effect of DA. Tyrosinase, which catalyzes the oxidation of DA to DA quionone (DAQ), accelerated the inhibitory effect of DA on LPS-induced NO production. These results suggest that DA attenuates LPS-induced NO production through the formation of DAQ in BV-2 cells.